From Petrochemical to Photosynthetic: Algae-Derived Polymers for Sustainable Industrial Applications - Dele-Afolabi, Temitope T.; Hanim, M.A. Azmah; Al-Qureshi, Hazim Ali (Journal of Research Updates in Polymer Science, 2025)
The demand for biopolymers made from photosynthetic organisms like algae is growing. This rise is driven by the global shift toward sustainable and renewable resources. This study examines the switch from conventional polymers based on petrochemicals to those derived from algae, emphasizing the potential of the latter for a variety of industrial uses. Algae, including both microalgae and macroalgae, are excellent feedstocks. They can produce various biopolymers such as alginate, carrageenan, agar, ulvan, and polyhydroxyalkanoates (PHAs). Algae grow quickly and do not compete with food crops, making them highly sustainable. Algae-derived biopolymers are useful in many applications, which include food packaging, biomedical devices, pharmaceuticals, and energy storage. Their key properties biodegradability, biocompatibility, film-forming ability, and gelling behaviormake them attractive alternatives. The study also discusses challenges such as scalability, processing methods, and market integration. It reviews the types of algae-based biopolymers, their production techniques, and performance characteristics. Overall, algae-derived polymers ultimately offer a viable route to more environmentally friendly industrial solutions, assisting in the development of a carbon-neutral and circular economy.